Evaluating the global warming potential of the fresh produce supply chain for strawberries,romaine/cos lettuces (Lactuca sativa), and button mushrooms (Agaricus bisporus) in Western Australia using life cycle assessment (LCA) - Gunady, Maria; Biswas, Wahidul; Solah, Vicky; James, Anthony (Elsevier Science, 2011)
A life cycle greenhouse gas (GHG) assessment of 1 kJ of strawberries, button mushrooms (Agaricus bisporus), and romaine/cos lettuces (Lactuca sativa) transported to retail outlets in Western Australia (WA) was examined and compared. The study included pre-farm, on-farm, and post-farm emissions. The pre-farm stage included GHG emissions from agricultural machinery and chemical production, and transport of raw materials (spawn, peat, and compost) in mushrooms. The on-farm stage included GHG emissions from agricultural machinery operation, chemical use, water for irrigation, waste generated, as well as electricity and energy consumption. The post-farm stage included transport of produce to Distribution Center (DC), storage in DC, and transport to retail outlets. The ‘hotspots’ or the stages that emit the highest GHG were determined for strawberries, button mushrooms and romaine/cos lettuces. The results have shown that the life cycle GHG emissions of strawberries and lettuces were higher than mushrooms due to intensive agricultural machinery operations during the on-farm stage. Mushrooms, however have significantly higher GHG emissions during pre-farm stage due to transport of peat, spawn, and compost.